1981
DOI: 10.1080/14640748108400828
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral transfer of inhibitory and excitatory eyelid conditioning in the rabbit

Abstract: In Experiment I, rabbits received training to establish a clicker as a conditioned inhibitor. In a subsequent test phase this stimulus was used as a signal for shock either to the eye reinforced during initial training or to the opposite eye. Learning to the clicker was slower in both conditions than in the appropriate control groups. The second experiment replicated the results of those subjects trained and tested with opposite eyes and ruled out the possibility that the slower learning was due to the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
3

Year Published

1983
1983
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 18 publications
4
41
3
Order By: Relevance
“…According to this view, the effect of a signal for the omission of pellets is indiscriminable from that of a signal for the omission of sucrose. Claims that Pavlovian inhibitors transfer across signals trained with different outcomes belonging to the same motivational class have been used to support this position (Nieto, 1984;Pearce, Montgomery, & Dickinson, 1981). The present fmdings of outcomedependent transfer are rather awkward for this point of view.…”
Section: Resultsmentioning
confidence: 84%
“…According to this view, the effect of a signal for the omission of pellets is indiscriminable from that of a signal for the omission of sucrose. Claims that Pavlovian inhibitors transfer across signals trained with different outcomes belonging to the same motivational class have been used to support this position (Nieto, 1984;Pearce, Montgomery, & Dickinson, 1981). The present fmdings of outcomedependent transfer are rather awkward for this point of view.…”
Section: Resultsmentioning
confidence: 84%
“…This result constituted weak support for outcome specificity of inhibition; however, two other studies in which aversive conditioningwas used provided no support for specificity. Pearce et al (1981) found that following conditioned inhibition training (A1, AX2) in the eyeblink conditioning procedure, rabbits showed roughly equivalent retardation of excitatory conditioning, relative to controls, whether the inhibitor was repeatedly paired with the same para-orbital shock used in conditioning or with shock to the other eye. There was no evidence for outcome specificity.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, an outcome-specific retardation-of-acquisition test was run (Pearce, Montgomery, & Dickinson, 1981). Before this test, the subjects first were given a minimal amount of additional backward training, and then they were segregated into two separate subgroups (n 5 8), each of which was subsequently given forward conditioning with the CSs and USs used previously.…”
Section: Methodsmentioning
confidence: 99%
“…All interpretations suggest a more elaborated characterization of the functional relationship between the CS and CR produced by the classical procedure (cf. Pearce, Montgomery, & Dickinson, 1981).…”
Section: Discussionmentioning
confidence: 99%